2015
DOI: 10.1097/ijg.0000000000000067
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Variability of Primary Congenital Glaucoma in a Spanish Family With Cyp1b1 Gene Mutations

Abstract: This clinical case reveals the etiological relationship between CYP1B1 mutations and PCG. In addition, it indicates a highly variable clinical picture associated with a single disease genotype mainly affecting disease onset and progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…Genotypes of patients PCG 49 and PCG 69 have previously been reported [6, 24]. Three patients had no brother or sister and were the only affected members of their families “Fig 1A”.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Genotypes of patients PCG 49 and PCG 69 have previously been reported [6, 24]. Three patients had no brother or sister and were the only affected members of their families “Fig 1A”.…”
Section: Resultsmentioning
confidence: 89%
“…Three patients had no brother or sister and were the only affected members of their families “Fig 1A”. Two of the patients were siblings (PCG 49, II:2 and II:4) and belonged to an seven member family with three affected subjects who carried the same genotype but manifested the disease at different ages “Fig 1A”, clearly illustrating the clinical variability present in CYP1B1 -associated glaucoma [24]. Three out of the five cases were compound heterozygotes, one was homozygote, and the last one was a single heterozygote.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important subgroup of patients of PCG associated with mutations in the CYP1B1 could have been excluded; these patients have more severe PCG, an earlier age of onset, greater corneal alterations, and comparatively more surgical procedures. 23,24 Our PCG cohort probably consisted of mild-to-moderate glaucoma cases. The average age at diagnosis in the PCG group was almost 2 years (23.24 AE 9.28 months); it is possible that most severe cases, which tend to be diagnosed at younger ages, were excluded, resulting in an underestimation of the difference in RNFL thickness between normal and PCG eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has reported that approximately 30% of Spanish PCG patients carry loss-of-function CYP1B1 variants, with most of these variants resulting in null genotypes6. Even among the cases with null enzymatic activity, remarkable phenotypic variation is present6715. These facts, along with the existence of incomplete penetrance and the discovery of a significant proportion of patients who carry non-dominant heterozygous CYP1B1 mutations6, suggest that more than one gene is involved in PCG.…”
mentioning
confidence: 97%